Development and application of a quadruplex TaqMan real-time fluorescence quantitative PCR assay for four porcine digestive pathogens - Wang, Haojie; Sun, Yue; Chen, Jianxing; Wang, Wei; Yu, Haibo; Gao, Caixia; An, Tongqing; Wang, Yue; Chen, Hongyan; Zhu, Liangquan; Jin, Zhimin; Yu, Changqing; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionSalmonella, Escherichia coli, Lawsonella intracellularis, and Brachyspira hyodysenteriae are the primary pathogens responsible for gastrointestinal diseases in pigs, posing a significant threat to the health and productivity of pig production systems. Pathogen detection is a crucial tool for monitoring and managing these infections.MethodsWe designed primers and probes targeting the invA gene of Salmonella, the 23S rRNA gene of Escherichia coli, the aspA gene of Lawsonella intracellularis, and the nox gene of Brachyspira hyodysenteriae. We developed a quadruplex TaqMan real-time quantitative PCR assay capable of simultaneously detecting these four pathogens.ResultsThis assay demonstrated high sensitivity, with detection limits of 100 copies/μL for the recombinant plasmid standards pEASY-23S rRNA, pEASY-aspA, and pEASY-nox, and 10 copies/μL for pEASY-invA. The standard curves exhibited excellent linearity (R2 values of 0.999, 0.999, 1, and 0.998, respectively) and high amplification efficiencies (93.57%, 94.84%, 85.15%, and 81.81%, respectively). The assay showed high specificity, with no cross-reactivity detected against nucleic acids from Streptococcus suis, porcine epidemic diarrhoea virus (PEDV), porcine transmissible gastroenteritis virus (TGEV), Pasteurella multocida, Clostridium perfringens, Gracilaria parapsilosis, porcine delta coronavirus (PDCoV), porcine group A rotavirus (GARV), and porcine teschovirus (PTV). The assay also exhibited excellent repeatability, with inter- and intra-assay coefficient of variation (CV) ranging from 0.15% to 1.12%. High concentrations of nucleic acids did not interfere with the detection of low concentrations, ensuring robust performance in complex samples. Among 263 diarrhoeic samples, the assay detected Salmonella in 23.95%, Escherichia coli in 26.24%, Lawsonella intracellularis in 33.84%, and Brachyspira hyodysenteriae in 22.43%.DiscussionThis quadruplex TaqMan qPCR assay offers a rapid, sensitive, and specific tool for the simultaneous detection of Salmonella, Escherichia coli, Lawsonella intracellularis, and Brachyspira hyodysenteriae in pigs.